Development Of An Audit Protocol For The Investigation Of A Contaminated Site - Singh, Amar (2010)
New and emerging policies around the globe aim to set standards for the protection of soil and groundwater. Soil and groundwater degradation is seen as the change required from the public, entrepreneurs and cultivators to take a serious view on the harm it is doing. Focus on protecting the soil and groundwater to meet the legislative requirements for the benefit of future generations. Issues on contaminated sites are reviewed and the shortfalls observed with the present regulatory standards for both national and international. To develop an audit protocol for the investigation of a contaminated site a review on specific standards and practices of Australia, Canada, United Kingdom and Germany on their existing audit protocol are assessed and lay emphasis on the gap and lacking elements. The proposed audit protocol was then develops and validated on a selected industrial premise by employing a due diligence approach which includes interview, site historical review, soil and groundwater sampling and analysis. The premise is located in the Prai Industrial Zone and used to be involved in the manufacturing of electronic products and assemblies. The due diligence audit was conducted to ensure that the premise is free from any environmental and regulatory non compliance, since there is a potential property transaction.